2014
DOI: 10.1017/s0960258513000391
|View full text |Cite
|
Sign up to set email alerts
|

Activation and regulation of primary metabolism during seed germination

Abstract: Seed germination is regulated in a concerted manner that involves generating growth potential in the embryo to overcome the mechanical resistance of the endosperm. The wake-up call of a dry seed includes the reorganization of subcellular structures and the reactivation of metabolism in a dense, oxygen-poor environment. Pools of unbound metabolites and solutes produced by the degradation of storage reserves, including starch, proteins and oils, in the embryo can contribute to the generation of the embryo growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 116 publications
(257 reference statements)
9
142
0
7
Order By: Relevance
“…Attention should be given to the fact that the germination speed and the seedling growth rate were inversely proportional to the content of CO 2 released, considering that the simple correlation coefficients were -0.92 and -0.88 (p < 0.05), respectively, which corroborates with those reported by Rosental et al (2014), whose respiratory activity is indicative of vigor and its reduction directly affects the speed and growth rate of the seedlings. The high coefficients of correlation between the concentration of CO 2 obtained with the percentage of emerged seedlings suggest that the methodology was efficient in the prediction of the establishment of seedlings in the field, however, temperatures lower than or equal to 25 o C allow the greater separation of the lots, resulting in greater sensitivity in detecting differences in physiological potential in Triticum aestevium seeds not detected by viability tests, therefore, with the potential to classify lots according to their performance potential.…”
Section: Lotsupporting
confidence: 85%
See 2 more Smart Citations
“…Attention should be given to the fact that the germination speed and the seedling growth rate were inversely proportional to the content of CO 2 released, considering that the simple correlation coefficients were -0.92 and -0.88 (p < 0.05), respectively, which corroborates with those reported by Rosental et al (2014), whose respiratory activity is indicative of vigor and its reduction directly affects the speed and growth rate of the seedlings. The high coefficients of correlation between the concentration of CO 2 obtained with the percentage of emerged seedlings suggest that the methodology was efficient in the prediction of the establishment of seedlings in the field, however, temperatures lower than or equal to 25 o C allow the greater separation of the lots, resulting in greater sensitivity in detecting differences in physiological potential in Triticum aestevium seeds not detected by viability tests, therefore, with the potential to classify lots according to their performance potential.…”
Section: Lotsupporting
confidence: 85%
“…The intense respiratory activity in the first hours of imbibition is necessary for the generation of the redox state (Rosental et al, 2014) and the energetic requirement is directed to the production of systems of removers of reactive forms of oxygen in seeds of lower physiological potential submitted to supra-optimal temperatures (Dantas et al, 2015).…”
Section: Determination Of Carbon Dioxide Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have indicated that the increase in AA concentration during germination is due to protein degradation, which results in the release of AA. The reduction in the AA concentration, typically at 3 and 5 das in these three species, has also been observed in Arabidopsis thaliana seeds after the application of a scarification treatment at 4 °C and in Lens culinaris and Pisum sativum seeds (Joosen et al 2013, Rosental et al 2014. In other species, an increase in the AA concentration during germination has also been observed (Kuo et al 2004).…”
Section: Mobilization Of Reservesmentioning
confidence: 61%
“…This observation corresponded with the finding that hydrolysis of starch reserves in the cotyledons commences after germination (Bewley et al 2013). The degradation of storage reserves including starch (and proteins) can contribute to the embryo growth potential (Rosental et al 2014).…”
Section: Discussionmentioning
confidence: 99%